2015
DOI: 10.14221/ajte.2015v40n11.6
|View full text |Cite
|
Sign up to set email alerts
|

I know how to add them, I didn't know I had to add them

Abstract: Jhagroo, J. R. (2015). I know how to add them, I didn't know I had to add them. Australian Journal of Teacher Education, 40(11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Further evidence supporting the interconnected nature of learning mathematics and language for ELs came from studies of the language of tasks, curriculum materials, or both. Several researchers found that textbook and task terminology, unfamiliar problem contexts, grammar, and syntax can be challenging for ELs (Jhagroo, 2015; Kazima, 2007; Lager, 2006; Novotná & Moraová, 2005; Ríordáin & O’Donoghue, 2011; Zahner, 2012). For example, Lager (2006) found that the use of technical terminology such as show and pattern affected ELs’ performance on generalization tasks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further evidence supporting the interconnected nature of learning mathematics and language for ELs came from studies of the language of tasks, curriculum materials, or both. Several researchers found that textbook and task terminology, unfamiliar problem contexts, grammar, and syntax can be challenging for ELs (Jhagroo, 2015; Kazima, 2007; Lager, 2006; Novotná & Moraová, 2005; Ríordáin & O’Donoghue, 2011; Zahner, 2012). For example, Lager (2006) found that the use of technical terminology such as show and pattern affected ELs’ performance on generalization tasks.…”
Section: Resultsmentioning
confidence: 99%
“…We found a number of research foci in this area as well as several cross-cutting themes. A number of authors attended to the need to value ELs’ ideas and resources (LópezLeiva et al, 2013; Matang & Owens, 2014; Setati, 2008), the role of providing ELs with quality mathematics experiences (e.g., Dominguez, 2011; McGraw & Rubinstein-Ávila, 2009; Razfar, 2012b; Turner & Celedón-Pattichis, 2011), roadblocks placed in ELs’ learning experiences (Barwell, 2014; Bautista Verzosa & Mulligan, 2013; Cho et al, 2015; Lager, 2006), and ways ELs supported their own learning through such practices as code switching (Clarkson, 2007), gesturing (Dominguez, 2005), and using other language strategies, like using a silent phase or a translation dictionary (Jhagroo, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation